The blast pathogen effector AVR-Pik binds and stabilizes rice heavy metal-associated (HMA) proteins to co-opt their function in immunity. - Kaori Oikawa; Koki Fujisaki; Motoki Shimizu; Takumi Takeda; Keiichiro Nemoto; Hiromasa Saitoh; Akiko Hirabuchi; Yukie Hiraka; Naomi Miyaji; Aleksandra Białas; Thorsten Langner; Ronny Kellner; et al. (PLoS Pathogens)
Intracellular nucleotide-binding domain and leucine-rich repeat-containing (NLR) receptors play crucial roles in immunity across multiple domains of life. In plants, a subset of NLRs contain noncanonical integrated domains that are thought to have evolved from host targets of pathogen effectors to serve as pathogen baits. However, the functions of host proteins with similarity to NLR integrated domains and the extent to which they are targeted by pathogen effectors remain largely unknown. Here, we show that the blast fungus effector AVR-Pik binds a subset of related rice proteins containing a heavy metal-associated (HMA) domain, one of the domains that has repeatedly integrated into plant NLR immune receptors. We find that AVR-Pik binding stabilizes the rice small HMA (sHMA) proteins OsHIPP19 and OsHIPP20. Knockout of OsHIPP20 causes enhanced disease resistance towards the blast pathogen, indicating that OsHIPP20 is a susceptibility gene (S-gene). We propose that AVR-Pik has evolved to bind HMA domain proteins and co-opt their function to suppress immunity. Yet this binding carries a trade-off, it triggers immunity in plants carrying NLR receptors with integrated HMA domains.